Social Dynamics of Entrepreneurship among Students of the Public Administration Study Program, Tadulako University - M. Kafrawi Al- Kafiah Samsu; Yulizar Pramudika Tawil; Risma Ariyani; Andi Famrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The author examines this issue with the aim of implementing the Tridharma of higher education through entrepreneurial socialization, which aims to develop entrepreneurial insights for students of the Public Administration Study Program, Faculty of Social and Political Sciences, so that it can be of benefit to society. This research is focused on knowing the interest in entrepreneurship among students of the Public Administration Study Program, Faculty of Social and Political Sciences, Tadulako University, and is expected to make a theoretical contribution to the development of student entrepreneurial interest. This study uses a qualitative descriptive method, and the results show that there are still many students who do not understand entrepreneurship; there is a lack of material to foster interest in entrepreneurship in lecture material; there is no proper role model for students; and there is a lack of space to hone knowledge about entrepreneurship. Therefore, further efforts are needed to increase understanding and interest in entrepreneurship among students of the Public Administration Study Program, Faculty of Social and Political Sciences, Tadulako University, through providing relevant material and developing appropriate platforms to facilitate entrepreneurial learning.